Performance Analysis of Sepic Fed LCLC Resonant Converter for EV Battery Charger - et. al., Dr. R. Arulmozhiyal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
EV’sare becoming more popular due to their eco-friendly nature. The existing topology of off board chargers are powered using a domestic meter. This results in high harmonic currents and hence, the domestic appliances get collapsed. Thus, to overcome this problem, this work proposes a novel charger unit which maintains power factor at unity. Thus, it contains two stages namely, DC-DC converter (SEPIC) at the first stage and 4 element resonant converter at the second stage. From the result, it is observed that the proposed changer exhibits better performance with low THD.